2018
DOI: 10.2147/rrtm.s160951
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genus <em>Rickettsia</em> in Central America

Abstract: In this paper, we present a historical review of rickettsiosis in Central America and also the most recent findings of Rickettsia in ectoparasites. All countries of Central America have records of rickettsiosis. Regarding the typhus group rickettsioses, there is clinical or serological evidence of Rickettsia prowazekii in Guatemala, Rickettsia typhi in Panama, Guatemala, and Costa Rica and unidentified species of the typhus group in El Salvador. Concerning spotted fever group rickettsiosis, there is serologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 80 publications
1
49
1
6
Order By: Relevance
“…Multilocus typing showed that 11 of these Rickettsia genotypes can be assigned to two validated Rickettsia species, namely R. amblyommatis (two genotypes) and R. bellii (nine genotypes). These two Rickettsia species are widely present among Central and South American ticks, each infecting more than 10 species 7,[11][12][13][21][22][23][24][25][26] . Their presence in French Guiana was therefore expected, but the observation of novel genotypes indicates the presence of important geographic variability: R. amblyommatis and R. bellii have probably radiated within their respective regions, including French Guiana, into different genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multilocus typing showed that 11 of these Rickettsia genotypes can be assigned to two validated Rickettsia species, namely R. amblyommatis (two genotypes) and R. bellii (nine genotypes). These two Rickettsia species are widely present among Central and South American ticks, each infecting more than 10 species 7,[11][12][13][21][22][23][24][25][26] . Their presence in French Guiana was therefore expected, but the observation of novel genotypes indicates the presence of important geographic variability: R. amblyommatis and R. bellii have probably radiated within their respective regions, including French Guiana, into different genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Since none of the 19 Rickettsia genotypes was previously described before this study, no evidence of their pathogenicity currently exists, even for those belonging to validated Rickettsia species. Indeed, although R. amblyommatis and R. bellii are commonly found in the ticks of French Guiana, and more broadly in American ticks 7,[11][12][13][21][22][23][24][25][26] , they have never been found in vertebrate hosts, suggesting that they are nonpathogenicspecies. Interestingly, while the Cayenne tick A. cajennense is one of the most common ticks found in French Guiana, blood-feeding on many different hosts, including humans 8,30,31 , R. amblyommatis (infecting here 25% of the A. cajennense specimens examined) were never detected in humans or animals: while French Guiana is an outermost region of the European Union, with technical and financial resources that close to European countries, no case was notified to date.…”
Section: Discussionmentioning
confidence: 99%
“…1. Riketsje z grupy TG różnią się od tych z grupy SFG brakiem możliwości polimeryzacji aktyny, zdolnością do zakażania jedynie cytoplazmy komórki gospodarza (SFG wykazują zdolność zakażania również jądra komórkowego), optymalną temperaturą wzrostu, zawartością par G-C w genomie, jak również brakiem białek błony zewnętrznej OmpA (posiadają jedynie białko OmpB) [4][5][6]. Genom bakterii z rodzaju Rickettsia zawiera od 1,1 do 2,3 Mb, przy czym może występować do 4 plazmidów.…”
Section: Taksonomiaunclassified
“…Rickettsia rickettsii (FMRR). Su amplia distribución abar ca varias ecorregiones en los tres bloques continentales, producto de una variable ecología que incluye varias es pecies de garrapatas como vectores confirmados, además de potenciales reservorios [1,7,8].…”
unclassified
“…Es ampliamente conocido que la FMRR produce signos y síntomas similares a otras enfermedades como el den gue, fiebre tifoidea, sarampión, gastroenteritis aguda, in fecciones por enterovirus, meningococcemia, infección gonocócica diseminada, sífilis secundaria, leptospirosis, vasculitis por complejos inmunes, púrpura trombocitopé nica autoinmune, mononucleosis infecciosa, ehrlichiosis, anaplasmosis entre otras [8,9]. No obstante, los casos de fiebre manchada por R. rickettsii se distinguen por los se veros efectos que provoca al endotelio de los vasos san guíneos de pequeño calibre en forma generalizada, con graves consecuencias [10].…”
unclassified